Improving principles of the construction sector business associations’ management systems under the inuence of hypercompetition: factor of «the markets deregulation process» - N. E. Kunyaev; L. M. Martynov; E. A. Starozhuk (Управление)
The «hypercompetition matrix» of management of the construction sphere modern organizations in the material and virtual business environment with the use of information and communication technologies was analyzed. The article’s purpose was the formation of the scientific basis for the management system improvement referred to modern organizations in terms of hypercompetitive material-virtual business environment. The main task was to formulate the function and development principles of the considered construction sphere business associations’ management system in the modern environment. The step-by-step procedure allowed to methodologically structured implement one of the hyper-competitive factors influence analysis on the construction sphere modern business associations’ management system. The process of markets deregulation, taking into account its exceptional features, impacts on the success factors was considered. This feature was selected from a number of others as the most relevant in the case of information and communication management in a hyper-competitive environment considering the development of a virtual environment based on information and communication technologies application. Seven principles of construction sphere modern business associations’ management systems improvement were defined.